Analisis keterampilan berpikir matematis siswa dengan critical thinking (fachione) untuk meningkatkan kemampuan literasi matematis pada materi kpk dan fpb - Dhimas Dwi Ardiantoro; Baru Yufron Kurniawan; Moch Daffa Muhaimin; Havif Wahyu Saputra; Rafiul Faisa Ramadhan; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to analyze students' mathematical thinking skills based on Facione's Critical Thinking indicators in improving mathematical literacy on the topics of Least Common Multiple (LCM) and Greatest Common Factor (GCF) in elementary school. The study employed a descriptive qualitative approach involving six fourth-grade students selected through purposive sampling, representing high, moderate, and low mathematical ability levels. Data were collected using mathematical literacy tests, semi-structured interviews, and documentation. Data validity was ensured through technique triangulation and member checking, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The analysis focused on six critical thinking indicators, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The findings are expected to provide a comprehensive description of students' mathematical thinking processes in solving mathematical literacy problems on LCM and GCF. This study also offers insights for teachers in designing mathematics instruction that integrates critical thinking and mathematical literacy to enhance students' problem-solving abilities in real-life contexts.